The Role of Thioredoxin System in Shank3 Mouse Model of Autism - Bazbaz, Wisam; Kartawy, Maryam; Hamoudi, Wajeha; Ojha, Shashank Kumar; Khaliulin, Igor; Amal, Haitham (Journal of molecular neuroscience, 2024)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by difficulties in social interaction and communication, repetitive behaviors, and restricted interests. Unfortunately, the underlying molecular mechanism behind ASD remains unknown. It has been reported that oxidative and nitrosative stress are strongly linked to ASD. We have recently found that nitric oxide (NO•) and its products play an important role in this disorder. One of the key proteins associated with NO• is thioredoxin (Trx). We hypothesize that the Trx system is altered in the Shank3 KO mouse model of autism, which may lead to a decreased activity of the nuclear factor erythroid 2-related factor 2 (Nrf2), resulting in oxidative stress, and thus, contributing to ASD-related phenotypes. To test this hypothesis, we conducted in vivo behavioral studies and used primary cortical neurons derived from the Shank3 KO mice and human SH-SY5Y cells with SHANK3 mutation. We showed significant changes in the levels and activity of Trx redox proteins in the Shank3 KO mice. A Trx1 inhibitor PX-12 decreased Trx1 and Nrf2 expression in wild-type mice, causing abnormal alterations in the levels of synaptic proteins and neurotransmission markers, and an elevation of nitrosative stress. Trx inhibition resulted in an ASD-like behavioral phenotype, similar to that of Shank3 KO mice. Taken together, our findings confirm the strong link between the Trx system and ASD pathology, including the increased oxidative/nitrosative stress, and synaptic and behavioral deficits. The results of this study may pave the way for identifying novel drug targets for ASD.